PENERAPAN LKS BERMUATAN NILAI-NILAI KARAKTER DALAM MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW PADA KELAS XI DI SMA NEGERI 11 PADANG - Asrad Hafizah; Yenni Darvina; Masril Masril (PILLAR OF PHYSICS EDUCATION, 2015)
Achievements of mastery learning physics students at SMAN 11 Padang were not optimal.These are caused by less optimal learning activities ,lack of cooperation, and undeveloped characters of students in the learning process. Moreover, learning model and teaching materials that commonly used have not been varied and Student Worksheet has not been charged character values. Therefore, this research aimed to determine the effect of applying the charged Student Worksheet character values in Jigsaw cooperative learning model in class XI SMAN 11 Physics Padang on learning outcomes of students’s competency attitudes, knowledge, and skills.Type of research was a quasi-experimental (Quasi-Experimental Research) with a research design form was Randomized Control Group Only Design. Population were all students in class XI SMA MIA 11 Padang who registered academic year 2014/2015 with a cluster random sampling technique. The research instrument used a form of observation sheet on the attitude of competencies, a written test on knowledge competencies, and rubring scor on skills competencies. Data were analyzed using two similarity test average used was the t. The results showed that the average of students learning outcomes in experimental class and control class on all competencies were sequentially: (81.38) and (68.9), (80.25) and (75 , 23), and (74.78) and (66.9). Based on the hypothesis test on all competencies as compared with the value of 1.98 tt. Therefore, can be concluded that the hypothesis "There is a significant impact on the application of the Student Worksheet charged character values in Jigsaw cooperative learning model in class XI SMAN 11 Padang" received on the real level of 0.05